Social Penetration Theory in SBY dan Merry Riana’s Communication in the Mentor - Ardi Winangun; Chobin Martanto; Edison Bonar Tua Hutapea (Civilization Research: Journal of Islamic Studies, 2026)
An intimate relationship between two people can develop through several factors, including the length of their interaction and equality in education, economic status, and culture. This study aimed to examine how such closeness was formed by analysing the communication between President Susilo Bambang Yudhoyono (SBY) and Merry Riana as recorded in the book The Mentor. The study employed qualitative text analysis with discourse analysis of the conversations between the two figures, supported by the Miles and Huberman analytical model. The results showed that Merry was able to reach the innermost layer of SBY’s personality, so that the fourth stage of social penetration was achieved. Through Merry’s questions, SBY revealed his most personal stories, including accounts that had previously been little known to the public. This success stemmed from a long period of interaction since 2011 and SBY’s family’s attention to Merry’s track record as a motivational speaker.